2011
DOI: 10.1182/blood-2011-02-338269
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia increases permeability of the blood-brain barrier by NMDA receptor-dependent regulation of adherens and tight junctions

Abstract: IntroductionMicrovessels are responsible for facilitating the exchange of nutrients between blood and tissue while maintaining a barrier against the undesired movement of other molecules. This barrier is most finely tuned and structurally competent at the interface between the blood and the brain, the blood-brain barrier (BBB). The BBB is formed by intercellular junctions that limit paracellular diffusion combined with a low-flux transcellular system that selectively transports molecules either into or out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(88 citation statements)
references
References 51 publications
4
80
0
4
Order By: Relevance
“…In the nucleus, pβ-cat forms a complex with FoxO1 and T-cell factor and the subsequent interaction of this complex with the claudin-5 promoter was shown to result in reduced levels of claudin-5. 20,29,30 In our study, we observed increased levels of p[S675]β-cat in the hSOD1 G93A cells compared with the wild-type cells indicating a mechanistic explanation for the reduced TJ protein levels. Furthermore, it was recently shown that the nuclear levels of β-cat are increased in whole lysates of ALS spinal cords of hSOD1 G93A mice, 31 pointing again to a direct involvement of mutant SOD expression in impaired barrier integrity due to an altered pathway responsible for TJ protein expression.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In the nucleus, pβ-cat forms a complex with FoxO1 and T-cell factor and the subsequent interaction of this complex with the claudin-5 promoter was shown to result in reduced levels of claudin-5. 20,29,30 In our study, we observed increased levels of p[S675]β-cat in the hSOD1 G93A cells compared with the wild-type cells indicating a mechanistic explanation for the reduced TJ protein levels. Furthermore, it was recently shown that the nuclear levels of β-cat are increased in whole lysates of ALS spinal cords of hSOD1 G93A mice, 31 pointing again to a direct involvement of mutant SOD expression in impaired barrier integrity due to an altered pathway responsible for TJ protein expression.…”
Section: Discussionsupporting
confidence: 55%
“…Thus, unphosphorylated FoxO1 is translocated to the nucleus, forming a complex with pβ-cat and T-cell factor and thereby repressing the claudin-5 expression. [18][19][20] To assess whether the expression of mutant SOD1 affects this pathway, we analyzed the phosphorylation states of β-cat, AKT, and FoxO1 by western blot (Figure 4). We observed increased levels of pβ-cat and decreased levels of pAKT in mutant bEnd.3 cells compared with SOD1 WT overexpressing cells ( Figures 4A and 4D).…”
Section: Furthermore Hsod1mentioning
confidence: 99%
“…Interestingly, in the present work we have observed effects by MK801 in our BBB in vitro model without using astrocytes indicating the presence of alternative pathways. Recently, deleterious effects of homocysteine onto the BBB were reported to be mediated by NMDAR [2]. Furthermore, we and others were able to show that MK801 alone can affect the proteome and the intracellular Ca-level of BBB models [16,17].…”
Section: Resultsmentioning
confidence: 59%
“…29,30 Previous studies from our and other labs have also shown that high Hcy levels impart significant influence in BBB opening and thus raise permeability. 3,[31][32][33] Therefore, we created BBB disruption model by using Hcy in bEnd.3 cells and to validate in vitro findings, we used genetically hyperhomocysteinemic CBS þ / À mice models for in vivo studies. Previous studies also described bEnd.3 cells as a convenient and useful model to study BBB functions.…”
Section: Discussionmentioning
confidence: 99%